Managing the Noodle Bowl: The Fragility of East Asian Regionalism - Richard E. Baldwin (Asian Development Bank (ADB), 2007)
The paper argues that East Asian regionalism is fragile because (i) each nation's industrial competitiveness depends on the smooth functioning of "Factory Asia" - in particular for intraregional trade; (ii) the unilateral tariff-cutting that created Factory Asia is not subject to WTO discipline (bindings); (iii) there is no "top-level management"; to substitute for WTO discipline, to ensure that bilateral trade tensions - tensions that are inevitable in East Asia - do not spill over into region-wide problems due to lack of cooperation and communication. This paper argues that the window of opportunity for East Asian vision was missed; what East Asia needs now is management, not vision. East Asia should launch a "New East Asian Regional Management Effort" with a reinforced ASEAN+3 leading the way. The first priority should be to bind the region's unilateral tariff cuts into the WTO.
hdl:11540/1848
Keywords: F15; 330; Asian integration; free trade agreement; best practices; Asian development